FAKTOR FAKTOR PENDUKUNG PENYEMBUHAN LUKA PERINEUM PADA IBU POST PARTUM - Purnamasari, Desy; Putri, Olga Meisya (Ensiklopedia of Journal, 2025)
The length of time it takes for perineal wounds to heal can be uncomfortable for new mothers and affect the frequency of painful infections. Perineal rupture-related occurrences have been linked to 21.1 million deaths worldwide, with 16.3 million of those deaths occurring in Southeast Asia. This study set out to identify the variables linked to the healing of perineal wounds. Using a cross-sectional design and successive sampling approaches, 30 samples with first and second degree lacerations were used. The REEDA scale instrument, formular record, and SPSS chi square analysis were used during the 30-day trial. The study's findings revealed that 0.003 <0.05 for the maternal age statistical test. Results of the statistical test for the parity variable are 0.030 <0.05. A statistical test of the degree of laceration variable yields 0.000 <0.05. Therefore, among postpartum moms, the degree of laceration, maternal age, and parity are related to the healing of perineal suture wounds. Mothers are advised to consider the condition when preparing for their subsequent pregnancy.Keywords: Postpartum, age, parity, laceration, perineal wound